Renewable Energy Power Generation Design Modeling Simulation on Solar Energy Sources and Coconut Shells Using Homer - Nefertiti Widiarini; Astrid Noviana Paradhita; Ni Komang Septia Noriska (Journal of Renewable Energy, Electrical, and Computer Engineering, 2025)
Using fossil fuels contributes to carbon dioxide and methane emissions that increasingly damage nature. Innovations in renewable energy that are more environmentally friendly with good energy supply chain management need to be implemented immediately. Indonesia is an archipelagic country with an imbalance in energy sufficiency figures in several regions, including Balikukup village in East Kalimantan. This condition hinders people's daily activities and is a significant obstacle to business activities. This research was conducted to design a zero-carbon renewable hybrid energy innovation that can preserve the environment and improve the community's economy using solar energy and coconut shells. The design was simulated using the HOMER application to find out how much potential and electricity the residents of Balikukup village would get. This study obtained a system configuration scenario: the marine product drying machine, which has a total production of 4,106 kWh/yr. This machine requires a PV capacity of 7,627 kW/yr, 18 batteries, and an inverter capacity of 1.62 kW. In addition, coconut shell briquettes can also optimize the marine product drying machine where 100 - 150 kg of coconut shell waste can increase the drying temperature to 60° - 70° C in a faster time of around 3 - 4 hours to reduce the weight of marine products from 5 - 8 kg to 1 - ½ kg.